“Loving-Knowing” Women and Horses: Symbolic Connections, Real Life Conflicts and “Natural Horsemanship” - Savvides, Nikki (Humanimalia, 2011)
This paper investigates the complexities of relations between women and horses. Through an analysis of literary material, it highlights the therapeutic and empowering potentials that arise as a result of their connection. It makes a discursive analysis of interview material gathered from twenty-two female Australian horse owners, and, in doing so, challenges the often held idea that women are ‘naturally’ affinitive with horses. The paper analyses the tension between feelings of love and familiarity and matters of conflict between women and their horses, and demonstrates that power plays in their relations may hinder the ability for woman and animal to get along. It reveals the ways in which women have overcome such problems by treating their horses as ‘companions’, allowing the therapeutic and empowering potentials of their relations with horses to be realized.